Rekonstruksi Hukum Ekonomi Syariah dalam Perspektif Maqashid Al-Shari'ah - Laylatul Istiqomah, May (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
The reconstruction of Islamic economic law is essential in addressing the dynamics of global economic development and the evolving needs of Muslim societies. This article aims to re-examine the normative and operational foundations of Islamic economic law through the lens of Maqashid al-Shari'ah, in order to establish a more inclusive, just, and contextual economic system. By employing a library research method and qualitative analysis, The findings of this study indicate that the reconstruction of Islamic economic law through the Maqashid al-Shari’ah approach is not merely a methodological necessity, but an epistemological imperative to address the complexities of global economic dynamics and the challenges faced by contemporary Muslim societies. Maqashid serves as a normative compass that balances text and context, as well as formal legality and substantive justice. By positioning maqashid as the foundation of reconstruction, Islamic economic law can be transformed into a system that is not only shari’ah-compliant but also socially transformative eliminating inequality, protecting rights, and establishing a progressive, solution-oriented, and universally beneficial Islamic economic order. Maqashid al-Shari’ah offers a constructive framework for adapting Islamic economic law to contemporary issues such as economic digitalization, financial inclusion, and consumer protection. This approach expands the scope of ijtihad within Islamic economic law without compromising the fundamental principles of shari’ah. The implication of such reconstruction is the strengthening of regulations grounded in the substantive values of Islam, rather than mere normative textualism.